ANALISIS SWOT DALAM STRATEGI PENINGKATAN MUTU PENDIDIKAN DI SMP NEGERI 11 BALIKPAPAN - Saifullah, Hanif; Sulfi Ardiansyah; Anis Widayati; Tri Wahyuni; Herlina; Nurlaili; Usfandi Haryaka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of SWOT analysis in improving the quality of education at SMP Negeri 11 Balikpapan. This research employed a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The study focused on identifying internal and external factors affecting school quality improvement through the SWOT approach, including strengths, weaknesses, opportunities, and threats. The results showed that SMP Negeri 11 Balikpapan is positioned in Quadrant I of the SWOT matrix, indicating that the school has strong internal conditions and significant external opportunities. The main strengths of the school include competent teachers, supportive school management, adequate facilities, and positive school culture. Meanwhile, external opportunities are reflected in government support, technological development in education, and strong community trust in the school. The study recommends the implementation of aggressive growth strategies through strengthening educational quality, improving teacher competencies, developing technology-based learning innovations, and enhancing collaboration with educational stakeholders. The findings indicate that SWOT analysis can be effectively used as a strategic tool in formulating sustainable educational quality improvement policies and strengthening school competitiveness.